Hadith #610 - Sunan al-Nasa'i - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; ibn Abbas; Ibn Jurayj ابن جريج; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Saleem bin Aswad, Abu al-Ash'atha سليم بن أسود أبو الشعثاء المحاربي (Sunan al-Nasa'i)
“I never saw the Messenger of Allah (ﷺ) combine any two prayers except in Al-Muzdalifah, and on that day he prayed Subh before its time.”
Grade:

Hadith #691 - Sunan al-Nasa'i - Ash'ath bin Abi al-Ash'atha أشعث بن أبي الشعثاء; Muhammad bin Mansur bin Da'ud محمد بن منصور بن داود الطوسي; Saleem bin Aswad, Abu al-Ash'atha سليم بن أسود أبو الشعثاء المحاربي; Sufyan bin 'Uyaynah سفيان بن عيينة; Umar bin Sa'id bin Abi Hussain عمر بن سعيد بن أبي حسين النوفلي (Sunan al-Nasa'i)
“One of the portents of the Hour will be that people will show off in building Masjids.”
Grade:

Hadith #692 - Sunan al-Nasa'i - Ja'far bin Awn bin Ja'far جعفر بن عون بن جعفر; Saleem bin Aswad, Abu al-Ash'atha سليم بن أسود أبو الشعثاء المحاربي (Sunan al-Nasa'i)
“I used to recite Qur’an to my father on the road, and if I recited a verse in which prostration was required, he would prostrate. I said: ‘O my father, do you prostrate on the street?’ He said: ‘I heard Abu Dharr say: “I asked the Messenger of Allah (ﷺ): ‘Which Masjid was built first?’ He said: ‘Al-Masjid Al-Haram.’ I said: ‘How long was there between them?’ He said: ‘Forty years. And the earth is a Masjid (or a place of prostration) for you, so wherever you are when
Grade:

Hadith #1196 - Sunan al-Nasa'i - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Aisha bint Abi Bakr; Amr bin 'Ali bin Bahr al-Bahli عمرو بن علي بن بحر الباهلي; Ash'ath bin Abi al-Ash'atha أشعث بن أبي الشعثاء; Masrouq bin al-Ajda' مسروق بن الأجدع; Saleem bin Aswad, Abu al-Ash'atha سليم بن أسود أبو الشعثاء المحاربي; Za'ida bin Qadama al-Thaqifi زائدة بن قدامة الثقفي (Sunan al-Nasa'i)
A man from among the companions of the Prophet (ﷺ) told him that he heard the Messenger of Allah (ﷺ) say: ‘If any one of you in praying, let him not lift his gaze to the sky, or his eyesight will be taken away.'”
Grade:

Hadith #1197 - Sunan al-Nasa'i - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Abu al-Ahwus, Salam bin Sulaym al-Hanafi أبو الأحوص سلام بن سليم الحنفي; Aisha bint Abi Bakr; Amr bin 'Ali bin Bahr al-Bahli عمرو بن علي بن بحر الباهلي; Ash'ath bin Abi al-Ash'atha أشعث بن أبي الشعثاء; Masrouq bin al-Ajda' مسروق بن الأجدع; Saleem bin Aswad, Abu al-Ash'atha سليم بن أسود أبو الشعثاء المحاربي (Sunan al-Nasa'i)
“I heard Abu Al-Ahwas saying to us in a gathering with Ibn Al-Musayyab when Ibn Al-Musayyab was sitting there, that he had heard Abu Dharr say: The Messenger of Allah (ﷺ) said: “Allah (SWT) continues to look upon His slave while he is praying, so long as he does not turn away. If he turns his face away, He turns away from him.”
Grade:

Hadith #1308 - Sunan al-Nasa'i - Aisha bint Abi Bakr; Ash'ath bin Abi al-Ash'atha أشعث بن أبي الشعثاء; Masrouq bin al-Ajda' مسروق بن الأجدع; Muhammad bin Bashar Bindar محمد بن بشار بندار; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس; Saleem bin Aswad, Abu al-Ash'atha سليم بن أسود أبو الشعثاء المحاربي; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“Ammar bin Yasir led the people in prayer and he made the prayer short. It was as if they disliked that, so he said: ‘Did I not do bowing and prostration properly?’ They said: ‘Yes.’ He said: ‘And I said a supplication that the Prophet (ﷺ) used to say:Allahumma bi ‘ilmikal-ghaiba wa qudratika ‘alal-khalqi ahini ma ‘alimtal-hayata khairan li, wa tawaffani idha ‘alimtal-wafata khairan li. Allahumma as’aluka khashyataka fil-ghaibi wash-shahadati wa as’aluka kalimatul-aqua
Grade:

Hadith #1616 - Sunan al-Nasa'i - Ash'ath bin Abi al-Ash'atha أشعث بن أبي الشعثاء; Masrouq bin al-Ajda' مسروق بن الأجدع; Muhammad bin Ibrahim bin al-Harith محمد بن إبراهيم بن الحارث; Saleem bin Aswad, Abu al-Ash'atha سليم بن أسود أبو الشعثاء المحاربي; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
The Prophet (ﷺ) came to him and Fatimah at night and said: “Won’t you pray?” I said: “O Messenger of Allah (ﷺ), our souls are in the hand of Allah and if He wants to make us get up, He will make us get up.” The Messenger of Allah (ﷺ) went away when I said that to him. Then as he was leaving I heard him striking his thigh and saying: But, man is ever more quarrelsome than anything.
Grade:

Hadith #3272 - Sunan al-Nasa'i - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; ibn Abbas; Muhammad bin Mansur bin Da'ud محمد بن منصور بن داود الطوسي; Saleem bin Aswad, Abu al-Ash'atha سليم بن أسود أبو الشعثاء المحاربي; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan al-Nasa'i)
“Seek the permission of women with regard to marriage.” It was said: “What if a virgin is too shy and remains silent?” He said: “That is her permission.”
Grade:

Hadith #3311 - Sunan al-Nasa'i - Muhammad bin 'Abdullah محمد بن عبد الله بن بزيع; Qatada قتادة; Sa'id bin Abi Sa'id; Saleem bin Aswad, Abu al-Ash'atha سليم بن أسود أبو الشعثاء المحاربي; Yazid bin Zari' يزيد بن زريع (Sunan al-Nasa'i)
“Mention was made to the Messenger of Allah of the daughter of Hamzah (as a potential wife). He said: ‘She is the daughter of my brother through breast-feeding.'” (One of the narrators) Shu’bah said: “Qatadah heard this from Jabir bin Zaid.”
Grade:

Hadith #3312 - Sunan al-Nasa'i - Abu al-Ahwus, Salam bin Sulaym al-Hanafi أبو الأحوص سلام بن سليم الحنفي; Ash'ath bin Abi al-Ash'atha أشعث بن أبي الشعثاء; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Masrouq bin al-Ajda' مسروق بن الأجدع; Saleem bin Aswad, Abu al-Ash'atha سليم بن أسود أبو الشعثاء المحاربي (Sunan al-Nasa'i)
“She is the daughter of my brother through breast-feeding, and what becomes unlawful (for marriage) through breast-feeding is the same as that which becomes unlawful through lineage.”
Grade:

Hadith #4837 - Sunan al-Nasa'i - Ash'ath bin Abi al-Ash'atha أشعث بن أبي الشعثاء; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Saleem bin Aswad, Abu al-Ash'atha سليم بن أسود أبو الشعثاء المحاربي; Wadah bin 'Abdullah al-Yashkari وضاح بن عبد الله اليشكري أبو عوانة (Sunan al-Nasa'i)
“I woman struck her co-wife, who was pregnant, with a rock and killed her Messenger of Allah ruled that a slave should be given (as Diyah) for the child in her woman, and that her Diyah should be paid by her ‘Asabah. They said:’ should we be penalized for one who neither after nor drank, or shouted or cried (at the moment of birth)? Such a one should be overlooked.’ He said: ‘Rhyming vase like the vase of the Bedouisn? It is what I say to (sahih)
Grade:

Hadith #4838 - Sunan al-Nasa'i - Abu al-Ahwus, Salam bin Sulaym al-Hanafi أبو الأحوص سلام بن سليم الحنفي; Ash'ath bin Abi al-Ash'atha أشعث بن أبي الشعثاء; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Saleem bin Aswad, Abu al-Ash'atha سليم بن أسود أبو الشعثاء المحاربي (Sunan al-Nasa'i)
‘O Messenger of Allah, she miscarried a boy whose hair had grown.’ The father of the killer said: “He is lying. By Allah he never cried or shouted (at the moment of birth), nor drank nor ate. Such a one should be overlooked.’ The Prophet said: ‘rhyming verse like the verse of the Jahiliyyah and of its soothsayers? A slave must be given (as Diyah) for the boy, ”’ Ibn ‘Abbes said; “One of then was Mulaikah and the other was Umm Ghatif.”
Grade:

Hadith #5396 - Sunan al-Nasa'i - al-Dahhak bin Mukhlad Abu 'Asim al-Nabil الضحاك بن مخلد أبو عاصم النبيل; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; ibn Abbas; Muhammad bin Ma'mar bin Rabi' محمد بن معمر بن ربعي القيسي البحراني; Saleem bin Aswad, Abu al-Ash'atha سليم بن أسود أبو الشعثاء المحاربي; Zakaria bin Ishaq al-Makki زكريا بن إسحاق المكي (Sunan al-Nasa'i)
When he came to the Messenger of Allah called him and said to him: “Allah is Al-Hakam (the Judge) and judgment is His. Why are you known as Abu Al-Hakam?” He said: “If my people differ concerning something, they come to me, and I pass judgment among them, and both sides accept it.” He said: “How good this is. Do you have any children?” He said: “I have Shuraih, and ‘Abdullah, and Muslim.” He said: “Who is the eldest of them?” He said: “Shuraih.” He said: “Then you ar
Grade:

Hadith #2690 - Sunan Abi Dawud - Abdur Rahman bin al-Mubarak al-'Aishi عبد الرحمن بن المبارك; ibn Abbas; Saleem bin Aswad, Abu al-Ash'atha سليم بن أسود أبو الشعثاء المحاربي; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Sufyan bin Habib al-Basri سفيان بن حبيب البصري (Sunan Abi Dawud)
‘Umar bin Al Khattab said “During the battle of Badr, the Prophet (ﷺ) took ransom”. Thereupon Allaah Most High sent down “It is not fitting for an Apostle that he should have prisoners of war until he hath thoroughly subdued the land. You look on the temporal goods of this world, but Allaah looketh to the Hereafter”. And Allaah is exalted in might and Wise. Had it not been for a previous ordainment from Allaah, a severe penalty would have reached you for the (ransom) that you took. A
Grade: Hasan Sahih

Hadith #2913 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; ibn Abbas; Muhammad Ibn Maslama; Musa bin Da'ud al-Dby موسى بن داود الضبي أبو عبد الله; Saleem bin Aswad, Abu al-Ash'atha سليم بن أسود أبو الشعثاء المحاربي (Sunan Abi Dawud)
Mu’adh bought the property of a Jew whose heir was a Muslim. He then narrated from the Prophet (ﷺ) to the same effect.
Grade: Da'if

Hadith #3799 - Sunan Abi Dawud - al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; ibn Abbas; Saleem bin Aswad, Abu al-Ash'atha سليم بن أسود أبو الشعثاء المحاربي (Sunan Abi Dawud)
Numaylah said: I was with Ibn Umar. He was asked about eating hedgehog. He recited: “Say: I find not in the message received by me by inspiration any (meat) forbidden.” An old man who was with him said: I heard AbuHurayrah say: It was mentioned to the Messenger of Allah (ﷺ). Noxious of the noxious. Ibn Umar said: If the Messenger of Allah (ﷺ) had said it, it is as he said that we did not know.
Grade: Da'if

Hadith #4139 - Sunan Abi Dawud - Aisha bint Abi Bakr; Ash'ath bin Abi al-Ash'atha أشعث بن أبي الشعثاء; Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; Masrouq bin al-Ajda' مسروق بن الأجدع; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Saleem bin Aswad, Abu al-Ash'atha سليم بن أسود أبو الشعثاء المحاربي; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: When one of you puts on sandals, he should put on his right one first, and when he takes them off, he should take off the left one first ; so that the right one should be the first to be put on and the last to be taken off.
Grade: Sahih

Hadith #62 - Jami' al-Tirmidhi - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; ibn Abbas; Maymuna bint al-Harith; Muhammad bin Yahya bin Abi 'Umar محمد بن يحيى بن أبي عمر العدني; Saleem bin Aswad, Abu al-Ash'atha سليم بن أسود أبو الشعثاء المحاربي; Sufyan bin 'Uyaynah سفيان بن عيينة (Jami' al-Tirmidhi)
“I and Allah’s Messenger would perform Ghusl for Janabah from one vessel.”
Grade:

Hadith #204 - Jami' al-Tirmidhi - Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Saleem bin Aswad, Abu al-Ash'atha سليم بن أسود أبو الشعثاء المحاربي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Waki' bin al-Jarrah وكيع بن الجراح (Jami' al-Tirmidhi)
“A man exited the Masjid after the Adhan for Asr had been called. So Abu Hurairah said: ‘As for this person, he has indeed disobeyed Abul Qasim.”
Grade:

Hadith #590 - Jami' al-Tirmidhi - Abu al-Ahwus, Salam bin Sulaym al-Hanafi أبو الأحوص سلام بن سليم الحنفي; Aisha bint Abi Bakr; Ash'ath bin Abi al-Ash'atha أشعث بن أبي الشعثاء; Masrouq bin al-Ajda' مسروق بن الأجدع; Saleem bin Aswad, Abu al-Ash'atha سليم بن أسود أبو الشعثاء المحاربي (Jami' al-Tirmidhi)
“I asked the Messenger of Allah about looking around during the Salat. He said: ‘It is a portion which the Shaitan snatches during a man’s prayer.'”
Grade:

Hadith #608 - Jami' al-Tirmidhi - Abu al-Ahwus, Salam bin Sulaym al-Hanafi أبو الأحوص سلام بن سليم الحنفي; Aisha bint Abi Bakr; Ash'ath bin Abi al-Ash'atha أشعث بن أبي الشعثاء; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Masrouq bin al-Ajda' مسروق بن الأجدع; Saleem bin Aswad, Abu al-Ash'atha سليم بن أسود أبو الشعثاء المحاربي (Jami' al-Tirmidhi)
“The Messenger of Allah would love to start with the right side when he purified himself, and when he combed, and when putting his sandals on.”
Grade:

Hadith #434 - Sunan Ibn Majah - Abu al-Ahwus, Salam bin Sulaym al-Hanafi أبو الأحوص سلام بن سليم الحنفي; Aisha bint Abi Bakr; Ash'ath bin Abi al-Ash'atha أشعث بن أبي الشعثاء; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Masrouq bin al-Ajda' مسروق بن الأجدع; Saleem bin Aswad, Abu al-Ash'atha سليم بن أسود أبو الشعثاء المحاربي; Sufyan bin Wky' bin al-Jrah سفيان بن وكيع بن الجراح; Umar bin 'Ubaid bin Abi Umayya عمر بن عبيد بن أبي أمية الطنافسي (Sunan Ibn Majah)
The Messeenger of Allah said: “Whoever catches one Rak’ah of the Subh before the sun rises, then he has caught it, and whoever catches one Rak’ah of the ‘Asr before the sun sets, then he has caught it.” (Sahih)Another chain with similar wording.
Grade:

Hadith #733 - Sunan Ibn Majah - Abu al-Ahwus, Salam bin Sulaym al-Hanafi أبو الأحوص سلام بن سليم الحنفي; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Ibrahim bin Mhajr bin Jabir إبراهيم بن مهاجر بن جابر; Saleem bin Aswad, Abu al-Ash'atha سليم بن أسود أبو الشعثاء المحاربي (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) said: ‘Allah and the angels send blessings upon the first row.’”
Grade:

Hadith #2021 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Aisha bint Abi Bakr; Ash'ath bin Abi al-Ash'atha أشعث بن أبي الشعثاء; Masrouq bin al-Ajda' مسروق بن الأجدع; Saleem bin Aswad, Abu al-Ash'atha سليم بن أسود أبو الشعثاء المحاربي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“You were my partner during the Ignorance period and you were the best of partners, you did not contend or dispute.”
Grade:

Hadith #2577 - Sunan Ibn Majah - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; ibn Abbas; Muhammad bin Muslim al-Ta'ifi محمد بن مسلم بن سوسن الطائفي; Musa bin Da'ud al-Dby موسى بن داود الضبي أبو عبد الله; Saleem bin Aswad, Abu al-Ash'atha سليم بن أسود أبو الشعثاء المحاربي (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) sent me to a village called Ubna, and said: “Go to Ubna in the morning and burn it.’”
Grade:

Hadith #4106 - Sunan Ibn Majah - Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Ibrahim al-Nakha'i إبراهيم النخعي; Saleem bin Aswad, Abu al-Ash'atha سليم بن أسود أبو الشعثاء المحاربي; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) said: ‘Do not tell lies about me, for telling lies about me leads to Hell (Fire).”
Grade: